Designing an Appropriate Model of Managers’ Decision-Making Styles by Considering Managers’ Spiritual Intelligence and Employees’ Organizational Citizenship Behavior - Nazeri, Mosayeb; Kamali, Mohammad Jalal; Hamzehee, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The present study aimed to design and test an appropriate model of managers’ decision-making styles based on managers’ spiritual intelligence and employees’ organizational citizenship behavior among managers and employees of Islamic Azad University in Sistan and Baluchestan Province. Methods and Materials: This study was conducted using an applied, descriptive-correlational design with a structural equation modeling approach. The statistical population included all managers and employees of Islamic Azad University in Sistan and Baluchestan Province during the 2020–2021 academic year. Sampling was performed using a stratified sampling method. Based on Cochran’s formula, 146 employees were selected from among 300 employees and 57 managers were selected from among 70 managers, resulting in a total sample of 203 participants. Data were collected using the General Decision-Making Style Questionnaire, the Spiritual Intelligence Self-Report Inventory, and the Organizational Citizenship Behavior Questionnaire. The reliability and validity of the instruments were confirmed through Cronbach’s alpha coefficients, composite reliability, and confirmatory factor analysis. Data analysis was conducted using descriptive statistics, Pearson correlation analysis, and structural equation modeling through SPSS and AMOS software. Findings: The results demonstrated that spiritual intelligence had a significant positive effect on rational decision-making style (β = 0.61, p = 0.001) and intuitive decision-making style (β = 0.37, p = 0.001), while it had a significant negative effect on avoidant decision-making style (β = -0.46, p = 0.001). Organizational citizenship behavior also positively influenced rational decision-making style (β = 0.42, p = 0.001) and negatively affected avoidant decision-making style (β = -0.34, p = 0.001). Furthermore, spiritual intelligence significantly predicted organizational citizenship behavior (β = 0.66, p = 0.001). Conclusion: The findings of the present study indicated that spiritual intelligence and organizational citizenship behavior play substantial roles in shaping managers’ decision-making styles within higher education institutions.